Wish-Granting Interventions Promote Positive Emotions in Both the Short and Long Term in Children with Critical Illnesses and Their Families - Hannah Roberts; Jenny Cook; Apple Lee; Wei Kok Loh; Nigel Teo; Joanne Su Yin Yoong; Marguerite Gorter-Stam (Children)
Background: Wish-granting interventions are recognized as positive experiences for children with critical illness and their families. While the positive effects have been shown in the immediate and short term, data on their long-term effects are lacking. Objectives: To evaluate the effects of wish-granting interventions on children and parents during and post intervention—both in the weeks after, and up to 5 years after—and to examine any differences between these two groups. Methods: A large-scale international survey was distributed to children (aged 13–17 years old in 2023) and their parents across 24 countries who received a wish-granting intervention in the preceding five years by Make-A-Wish Foundation International. Primary outcomes were positive emotions experienced by children and parents during and after the intervention (short term and long term). The secondary outcomes assessed were negative emotions in wish children, and to what extent children and parents felt the intervention created a sense of normalcy, benefitted other family members, created a happy memory, and gave relief from medical treatment, plus the perceived importance of wish-granting interventions. Results: The responses of 535 children and 1062 parents were analyzed. Both groups reported increases in positive emotions during the early intervention stages, peaking when the wish was granted and persisting in the short and long term. No significant differences were found between children and parents during wish-granting or after the intervention. Negative emotions were reported by a minority of children. Over 80% of children and parents felt the intervention created a happy memory and provided relief from their medical treatments. Nearly all children (96.8%) and parents (95.4%) viewed a wish-granting intervention as important for children with a critical illness. Conclusions: Wish-granting interventions can provide positive emotional benefits to both children and their families in both the short and long term.